1978
DOI: 10.1055/s-0028-1104816
|View full text |Cite
|
Sign up to set email alerts
|

Propafenon und Lidoflazin bei chronischem Vorhofflimmern und -flattern

Abstract: 60 patients with chronic atrial fibrillation and flutter were randomly allotted to two groups and treated alternately with two different therapy regimes. 30 patients (group I) received lidoflazine in increasing dosage up to 480 mg/24 h and in cases where there was no conversion to sinus rhythm propafenon in a maximal daily dosage of 1800 mg orally. The duration of treatment was limited to 4 days for each substance. 30 patients (group II) were treated in the reverse order, i.e. propafenon and in cases of ineffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Early after the drug's release, Beck et al (126) reported a 41 % conversion rate in chronic AF. Later on, Vita et al (127) reported a disappointing success rate for cardioversion of 9% for propafenone and 4% for placebo using intravenous propafenone.…”
Section: I90mentioning
confidence: 99%
See 1 more Smart Citation
“…Early after the drug's release, Beck et al (126) reported a 41 % conversion rate in chronic AF. Later on, Vita et al (127) reported a disappointing success rate for cardioversion of 9% for propafenone and 4% for placebo using intravenous propafenone.…”
Section: I90mentioning
confidence: 99%
“…Use in Paroxysmal Supraventricular Tachycardia Since the availability of radiofrequency ablation techniques, the role of pharmacological therapies for the long-term management of PSVT has narrowed. Nevertheless, propafenone has been used successfully for PSVT in a number of trials (116,120,126,(131)(132)(133)(134), although some have been limited to electrophysiologic studies (37, [135][136][137][138][139][140][141][142].…”
Section: I90mentioning
confidence: 99%